2018
DOI: 10.1002/slct.201800719
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Catalytic Activity in a Series of Push‐Pull Dicyanopyrazine/Dicyanoimidazole Photoredox Catalysts

Abstract: A series of dicyanopyrazine and dicyanoimidazole derived push‐pull molecules have been prepared and further investigated as photoredox catalysts. The fundamental properties of the catalysts were studied by DSC, X‐ray analysis, absorption/emission spectra, and electrochemistry and were completed with the DFT results. The catalytic activity has been evaluated in visible light induced α‐functionalization of amines (cross‐dehydrogenative coupling and annulation reaction of tetrahydroisoquinolines). Thorough struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 68 publications
1
28
0
Order By: Relevance
“…When using the strong Brønsted acids, i.e., TFA, TfOH and TsOH, no reaction was found (entry 10), which is most likely due to the generation of insoluble pyridinium salts from 1 with acids, thus hampering the reaction proceeding. Subsequently, a series of mixed solvents were evaluated (entries [11][12][13][14]; this evaluation was engaged in enhancing the solubility of NaH 2 PO 4 in the reaction system. To our delight, 9 was obtained in 93% yield when using mixed THF/CH 2 Cl 2 in a 1 : 1 ratio as the solvent system (entry 12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When using the strong Brønsted acids, i.e., TFA, TfOH and TsOH, no reaction was found (entry 10), which is most likely due to the generation of insoluble pyridinium salts from 1 with acids, thus hampering the reaction proceeding. Subsequently, a series of mixed solvents were evaluated (entries [11][12][13][14]; this evaluation was engaged in enhancing the solubility of NaH 2 PO 4 in the reaction system. To our delight, 9 was obtained in 93% yield when using mixed THF/CH 2 Cl 2 in a 1 : 1 ratio as the solvent system (entry 12).…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the reactions of N-aryl glycines with 2-(2-enynyl)pyridine (2), products 9-16 were obtained in 79 to 96% yields. Electron-donating substituents on the N-aryl ring of glycines (10)(11)(12)(13) were benecial to chemoselectivity, presenting good to excellent yields. Moreover, although electron-withdrawing groups attenuated reactivity, introducing an extra electron-donating substituent could afford products 13 and 15 with equally satisfactory results.…”
Section: Resultsmentioning
confidence: 99%
“…This polarized system shows an effective CT character (Figure 19). In strong contrast to CDCB PCs, their weak fluorescence indicates a short S 1 lifetime (<1 ns) [41] . Hence, DPZ PCs exclusively react in their T 1 state.…”
Section: Bimodal Organic Photocatalystsmentioning
confidence: 95%
“…In strong contrast to CDCB PCs,t heir weak fluorescence indicates as hort S 1 lifetime (< 1ns). [41] Hence,D PZ PCs exclusively react in their T 1 state.B ureš and co-workers suggested that this fast decay may be due to the heavy sulfur atom effect increasing the intersystem crossing rate from S 1 to T 1 .T wo structural features can be tuned to optimize the lifetime of the CT state of DPZ PCs: 1) the EDGs at positions 5a nd 6, and 2) the electron-withdrawing heterocyclic core,w ith the second possibility having an inferior impact.…”
Section: Structure-property Relationships Of the Dpz Photocatalystsmentioning
confidence: 99%
See 1 more Smart Citation